PENGARUH PELAKSANAAN PEMERIKSAAN PAJAK TERHADAP PENINGKATAN KEPATUHAN WAJIB PAJAK BADAN PADA KANTOR PELAYANAN PAJAK PRATAMA KUPANG - Pello, Selfiana (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2023)
This research analyzes the effect of implementing tax audits on increasing corporate taxpayer compliance at the Kupang Pratama Tax Service Office. The analysis used in this research is simple linear regression analysis. Tax Audit as the independent variable and Corporate Taxpayer Compliance as the dependent variable. The data source for this research is secondary data, namely data that has been processed by the Kupang Pratama Tax Service Office. The research results show that tax audits have a significant effect on corporate taxpayer compliance. This means that good taxpayer compliance can be achieved if the number of tax audits carried out by the tax inspector is high. Because the purpose of the audit is to test taxpayer compliance. This explains that tax audit actions can increase corporate taxpayer compliance at the Kupang Pratama Tax Service Office.